Analisis Pengelolaan Arsip Dinamis Aktif Surat di Sekolah Menengah Atas Negeri 78 Jakarta Barat - Amrita Dyah Lestari; Riyan Adi Putra; Mukmin Suprayogi (Librarianship in Muslim Societies, 2022)
Records management is something that is very important and cannot be separated in the management of an organization or agency. For a school, archives are very important as proof of the results of the school's accreditation assessment of the eight components of the national education standard. Therefore, every school must be able to have good archive management to support accreditation activities. This study aims to explain the management of active mail archives at Sekolah Menengah Atas Negeri (SMAN) 78 West Jakarta which already has A Accreditation. there are some things that are still not available. There are several things that are not yet available in the management of active mail archives at SMAN 78, namely: (1) the means of storing letters that are owned are still incomplete; (2) do not have books or proof of borrowing in the use of active mail dynamic archives; (3) does not yet have an Archive Retention Schedule (JRA) and a complete destruction report. These three things happen because the management of active mail archives is still done manually and the limited ability and knowledge of Human Resources (HR) in the archives field, as well as efforts to overcome obstacles have not been carried out optimally. Based on this, the researchers recommend to SMAN 78 that: (1) the management of active mail archives is carried out electronically; (2) Adding types and units of letter storage facilities and infrastructure; (3) Adding human resources devoted to managing letters or improving the capabilities of existing human resources through training in the field of archives, especially regarding archive disposition.